Evaluation of hepatoprotectve activity and isolation of 2-(3, 4-dihydroxy phenyl)-7-hydroxy-3-(2-hydroxy ethoxy) 4-H-chromen-4one from column fractions of leaves of the extract of Crataeva magna. - sovan pattanaik; Sudam Chandra Si; Abhisek Pal; Siva Shankar Nayak (International Journal of Phytomedicine, 2013)
Nature is only source of hepatoprotective drugs in modern medicine to prevent and treat drug-induced liver damage. The alcoholic extract of fresh leaves of the plant Crataeva magna, previously reported for its hepatoprotective activity was fractionated into three parts to chemically identify the most potent bioactive fraction. The current study was designed to evaluate the hepatoprotective activity, isolation and characterization property of effective column fractions of the leaves of the plant Crataeva magna. The hepatopreventive effect of the column fractions (F1, F2 and F3) of the leaves of the plant were evaluated by measuring the levels of serum liver damage marker enzyme such as alanine transaminase, aspartate transaminase, alkaline phosphatase, total and direct bilurubin. As per the result, since the F3 fraction of the extract showing out the significant reduction in the elevated serum level which can be compared with the standard drug silymarin therefore, phytochemical investigation of the F3 fractions led to the identify the structure of the flavonoid compound which was established by spectroscopic methods (UV, IR, 1H NMR, 13C NMR and EI-MS) as 2-( 3, 4-Dihydroxy Phenyl )-7-Hydroxy-3-( 2-Hydroxy Ethoxy) 4-H-Chromen-4one.